The impact of extra-domain structures and post-translational modifications in the folding/misfolding behaviour of the third PDZ domain of MAGUK neuronal protein PSD-95. - Javier Murciano-Calles (Public Library of Science (PLoS), 2014)
The modulation of binding affinities and specificities by post-translational modifications located out from the binding pocket of the third PDZ domain of PSD-95 (PDZ3) has been reported recently. It is achieved through an intra-domain electrostatic network involving some charged residues in the β2-β3 loop (were a succinimide modification occurs), the α3 helix (an extra-structural element that links the PDZ3 domain with the following SH3 domain in PSD-95, and contains the phosphorylation target Tyr397), and the ligand peptide. Here, we have investigated the main structural and thermodynamic aspects that these structural elements and their related post-translational modifications display in the folding/misfolding pathway of PDZ3 by means of site-directed mutagenesis combined with calorimetry and spectroscopy. We have found that, although all the assayed mutations generate proteins more prone to aggregation than the wild-type PDZ3, those directly affecting the α3 helix, like the E401R substitution or the truncation of the whole α3 helix, increase the population of the DSC-detected intermediate state and the misfolding kinetics, by organizing the supramacromolecular structures at the expense of the two β-sheets present in the PDZ3 fold. However, those mutations affecting the β2-β3 loop, included into the prone-to-aggregation region composed by a single β-sheet comprising β2 to β4 chains, stabilize the trimeric intermediate previously shown in the wild-type PDZ3 and slow-down aggregation, also making it partly reversible. These results strongly suggest that the α3 helix protects to some extent the PDZ3 domain core from misfolding. This might well constitute the first example where an extra-element, intended to link the PDZ3 domain to the following SH3 in PSD-95 and in other members of the MAGUK family, not only regulates the binding abilities of this domain but it also protects PDZ3 from misfolding and aggregation. The influence of the post-translational modifications in this regulatory mechanism is also discussed.